Analisis Kesulitan Membaca Siswa Tunagrahita Kelas Iv di Skh Negeri 01 Kota Serang - Nupus, Sohiyati; Fadliansyah, Fauzi; Maria Oktaviani, Anna (Arden Jaya Publisher, 2025)
This research aims to analyze the reading difficulties experienced by fourth-grade students with intellectual disabilities at SKH Negeri 01 Kota Serang using a descriptive qualitative method. The research data were collected through observation, interviews, and documentation with the research subjects consisting of teachers, fourth-grade students with intellectual disabilities, and parents. The findings show that students with intellectual disabilities still face difficulties in recognizing letters, combining syllables, reading simple words, and understanding texts. These obstacles are influenced by internal factors such as limited memory, concentration, and learning motivation, as well as external factors such as family support and the school environment. The strategies used by teachers to overcome reading difficulties include the syllabic reading method, visual media, repetition of materials, and an individualized approach tailored to students’ needs. The conclusion of this study is that reading difficulties among students with intellectual disabilities can be minimized through appropriate teaching strategies, teacher patience, and a supportive learning environment.